Single junction photovoltaic cell and sub-modules in optimization of solar farms - Sua, Lutfu S.; Balo, Figen (Elsevier B.V., 2019)
Turkey has a great potential in terms of renewable energy sources. Particularly, this potential comes to the fore in solar energy. Compared to the rest of Europe and other countries worldwide, Turkey has a very large level of annual sunshine period. One of the main elements used to produce electricity from solar energy in solar farms is solar cells. They produce direct current by converting the solar radiation directly onto the solar energy. In order to increase the power output, several solar cells are connected to each other in parallel or in series and mounted on a surface. This structure is called the solar cell module or photovoltaic module. If necessary, these modules can be connected to each other in series or parallel, to create a series of photovoltaic. For high efficiency photovoltaic cycle, it is necessary to improve the structural and electrical properties of the material to optimize the forbidden energy range and to use the most appropriate combination in the choice of the heterocline. In addition, the fact that the selected material can be produced economically at large scale is one of the conditions and it is desired that the sensitivity to the environment is considered during the use of this material. There are many types of solar cells in the market. Recently, 3rd generation solar cells from different materials have taken their place in the market. In a photovoltaic cell, the key operating parameters are efficiency, area, fill factor, and current-voltage (I-V) characteristics. This study's aim is determining the photovoltaic performance and comparing the solar cells fabricated in different types according to key operating parameters. © 2019 The Authors. Published by Elsevier B.V.
3rd World Conference on Technology, Innovation and Entrepreneurship, WOCTINE 2019 -- 21 June 2019 through 23 June 2019 -- Istanbul -- 141488
Keywords: Data Analysis; Photovoltaic; Renewable Energy; Solar cell; Solar energy